Brain‐responsive neurostimulation in patients with medically intractable seizures arising from eloquent and other neocortical areas. (7th April 2017) - Jobst, Barbara C.; Kapur, Ritu; Barkley, Gregory L.; Bazil, Carl W.; Berg, Michel J.; Bergey, Gregory K.; Boggs, Jane G.; Cash, Sydney S.; Cole, Andrew J.; Duchowny, Michael S.; Duckrow, Robert B.; Edwards, Jonathan C.; et al.
Summary: Objective: Evaluate the seizure‐reduction response and safety of brain‐responsive stimulation in adults with medically intractable partial‐onset seizures of neocortical origin. Methods: Patients with partial seizures of neocortical origin were identified from prospective clinical trials of a brain‐responsive neurostimulator (RNS System, NeuroPace). The seizure reduction over years 2–6 postimplantation was calculated by assessing the seizure frequency compared to a preimplantation baseline. Safety was assessed based on reported adverse events. Additional analyses considered safety and seizure reduction according to lobe and functional area (e.g., eloquent cortex) of seizure onset. Results: There were 126 patients with seizures of neocortical onset. The average follow‐up was 6.1 implant years. The median percent seizure reduction was 70% in patients with frontal and parietal seizure onsets, 58% in those with temporal neocortical onsets, and 51% in those with multilobar onsets (last observation carried forward [LOCF] analysis). Twenty‐six percent of patients experienced at least one seizure‐free period of 6 months or longer and 14% experienced at least one seizure‐free period of 1 year or longer. Patients with lesions on magnetic resonance imaging (MRI; 77% reduction, LOCF) and those with normal MRI findings (45% reduction, LOCF) benefitted, although the treatment response was more robust in patients with an MRI lesion (p = 0.02, generalized estimating equation [GEE]). There were no differences in the seizure reduction in patients with and without prior epilepsy surgery or vagus nerve stimulation. Stimulation parameters used for treatment did not cause acute or chronic neurologic deficits, even in eloquent cortical areas. The rates of infection (0.017 per patient implant year) and perioperative hemorrhage (0.8%) were not greater than with other neurostimulation devices. Significance: Brain‐responsive stimulation represents a safe and effective treatment option for patients with medically intractable epilepsy, including adults with seizures of neocortical onset, and those with onsets from eloquent cortex.